Causal Relationship Between Depression, Sleep Disorders, and Constipation: A Mendelian Randomization and Mediation Analysis - Wang JX; Wei KY; Lin W; Liu YJ (Psychology Research and Behavior Management, 2025)
Jun-Xi Wang,1,* Kai-Yan Wei,2,* Wei Lin,1 Yi-Juan Liu2 1Endoscope Center, The First Affiliated Hospital of Fujian Medical University, Fuzhou, 350005, People’s Republic of China; 2Department of Gastroenterology, The First Affiliated Hospital of Fujian Medical University, Fuzhou, 350005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi-Juan Liu, Department of Gastroenterology, The First Affiliated Hospital of Fujian Medical University, No. 20 Chazhong Road, Taijiang District, Fuzhou, 350005, People’s Republic of China, Tel +86 13599415881, Fax +86 0591-87981695, Email liuyijuanlyj@163.comObjective: The study aims to investigate the causal relationship between depression, sleep disorders, and constipation using multivariable Mendelian randomization (MR) and mediation MR analysis. Additionally, the potential mediating effects of sleep disorders in the association between depression and constipation were evaluated.Methods: Genome-wide association study (GWAS) data were utilized to identify genetic variants associated with depression, sleep disorders, and constipation as instrumental variables (IVs). The inverse-variance weighted (IVW) method was applied as the primary analytical approach. The mediating role of sleep disorders was assessed through multivariable MR and mediation MR analysis, and sensitivity analyses were conducted to assess the robustness of the findings.Results: Depression was associated with a significantly increased risk of constipation (OR 1.26, 95% CI 1.11– 1.44, P = 0.00034, IVW). Reverse MR analysis did not demonstrate a significant effect of constipation on depression (P = 0.086). According to mediation MR analysis, sleep disorders significantly mediated the causal association between depression and constipation, with a mediation rate of 13%. Sensitivity analyses supported the consistency and robustness of the findings.Conclusion: Findings from this study provide evidence of a causal relationship between depression and constipation, with sleep disorders serving as a partial mediator. These findings offer novel insights into the mechanisms of depression-related constipation, highlighting the potential role of sleep disturbances as a therapeutic target.Keywords: constipation, depression, mediation, Mendelian randomization, sleep disorder